STUDI LITERATUR PENGGUNAAN SAMPAH PLASTIK MENJADI PRODUK KREATIF - NI MADE NIA BUNGA SURYA DEWI (SOSIAL SAINS DAN TEKNOLOGI, 2022)
According to a study from the Indonesian Institute of Science (LIPI) in 2018 it was estimated that around 0.26 million ~ 0.59 million tons of this plastic flows into the sea and plastic waste in Indonesia reaches 66 million tons per year. The plastic waste recycling system has also not worked well in Indonesia, as well as the awareness of the people not to litter. Many Indonesian people also do not care about the dangers of plastic waste and the use of  single-use plastic bags. So it is not surprising that Indonesia is the largest waste contributor country in Southeast Asia and also number two in the world. The composition is 75% consisting of organic waste and only 25% inorganic waste. Organic waste has been widely used as material for making compost, briquettes and biogas, but inorganic waste is still very limited in its management. Seeing that the potential for inorganic waste is large, it is not impossible to be able to use the existing plastic waste to be converted into useful products. Moreover, the creations of plastic waste are no less competitive with factory-made products and of course have a selling power that can generate profits.